DEVELOPMENT OF RELIGIOUS AND MORAL VALUES ON 4-5 YEARS OLD CHILDREN IN IMITATING PRAYER MOVEMENT (SHALAT) USING SIMULATION AND REWARDING METHODS - Wahyu, Wahyu; Maimunah, Maimunah (Indonesian Researcher Society for Science Technology and Education (IDREST) Publisher, 2018)
The objectives of this study are to identify the description of teacher activity in performing steps of simulation method added by giving reward, children activity in learning as well as the result of children?s religious and moral values development in imitating prayer movement. This research is qualitative that using classroom action research type that taking place on Akhlaqul Karimah Kindergarten East Banjarmasin District group A. The research results show the improvement of religious and moral values in imitating prayer movement using simulation method and giving reward can improve teacher?s and children activity from cycle I improved to cycle II and the development results of children?s religious and moral values from Cycle I and Cycle II also improved.